Evaluation of the peripheral visual performance of DIMS spectacle lenses versus single vision lenses - Liu, Kenneth Ka King; Zhang, Han Yu; Leung, Daisy Ka Yan; Lam, Carly Siu Yin (Frontiers in Neuroscience, 2024)
PurposeThis study evaluates differences in the visual field performance when wearing the Defocus Incorporated Multiple Segments (DIMS) spectacle lens compared to wearing a conventional single vision (SV) spectacle lens.MethodsTwenty-one children aged 9–14 years with spherical equivalent refraction (SER) between −1.13D to −4.75D were recruited. Mid-peripheral near visual acuity (NVA) under room lighting condition (500 lux ±10%) was measured using DIMS and SV lenses, respectively. Automated static perimetry (Zeiss, Humphrey Visual Field HFA 750i) with SITA Fast 30–2 protocol was used to investigate the visual field sensitivity. During the test, the study lens (Plano DIMS or SV lens) were inserted into the lens holder in front of the trial lenses with each child’s compensated prescription.ResultsThree children were not able to complete the reliable visual tests due to fixation losses (>20%) or high false positive rate (>15%) while 18 children successfully completed the test. The mean visual field sensitivity was 29.2 ± 3.7 decibels (dB) and 29.3 ± 3.5 dB when wearing DIMS and SV lens, respectively. The mean sensitivity differences between DIMS and SV lens among 76 locations ranged from −2.4 ± 3.9 dB to 1.6 ± 3.9 dB. No statistically significant difference in sensitivity was observed across 76 locations within the central 30o between DIMS and SV lens (Wilcoxon signed rank test with bonferroni correction for multiple comparisons, p > 0.00065). Compared to SV lens, 0.05 logarithm of minimal angle of resolution (logMAR) reduction in mid-peripheral NVA in all 4 quadrants (Superior, Temporal, Inferior and nasal, p < 0.05) was noted with the DIMS lens (N = 18). However, no statistically significant correlation was found between the mid-peripheral NVA and visual sensitivity at the specific locations.ConclusionAlthough the mid-peripheral NVA was slightly reduced using DIMS lens, wearing DIMS lens did not change the children’s visual sensitivity to detect the static stimulus within 30o visual field when compared to wearing SV lens.